1995
DOI: 10.1136/bjo.79.4.335
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapeutic keratectomy for bullous keratopathy.

Abstract: Aims-This study was designed to investigate the therapeutic potential of excimer laser for recurrent painful erosions in patients not suited to treatment with penetrating keratoplasty. Methods-Phototherapeutic keratectomy (PTK) with the excimer laser was performed prospectively on a series of 13 eyes of 12 patients with recurrent corneal erosions in connection with bullous keratopathy of varied aetiology. The main complaint of the patients before the treatment was frequent attacks of pain. The patients selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
10

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 21 publications
3
50
0
10
Order By: Relevance
“…Several studies reported PTK to be elective in the management of patients with bullous keratopathy from a variety of etiologies; they reported that the bullae resolve and pain is abolished in a large proportion of patients treated with a superficial ablation [19,20].…”
Section: Phototherapeutic Keratectomy (Ptk)mentioning
confidence: 99%
“…Several studies reported PTK to be elective in the management of patients with bullous keratopathy from a variety of etiologies; they reported that the bullae resolve and pain is abolished in a large proportion of patients treated with a superficial ablation [19,20].…”
Section: Phototherapeutic Keratectomy (Ptk)mentioning
confidence: 99%
“…Because patients with BK can experience severe pain, many clinical and surgical interventions intending to improve the quality of life for these patients can be attempted while they are waiting for a donor cornea or when visual potential is poor and transplant is contraindicated. Previous studies suggested that ASP and AMT are efficient treatments for pain relief in patients with advanced BK (3,(8)(9)(10)(11)(12) . Frequently, UBM is important for planning the surgical approach when there is potential for restoring vision in eyes with advanced BK and corneal opacity due to severe edema.…”
Section: Discussionmentioning
confidence: 99%
“…Other treatments can be used for patients with no potential for vision restoration or while patients are waiting for a corneal graft. Such treatments include the use of topical 5% NaCl hypertonic solution, non-steroidal anti-inflammatory agents, antiglaucomatous medications, therapeutic contact lenses, conjunctival flaps, electrocauterization, annular keratotomy, phototherapeutic keratectomy, anterior stromal puncture (ASP), and amniotic membrane transplantation (AMT) (3,(8)(9)(10)(11)(12) . In order to compare the effectiveness of ASP and AMT for the relief of pain in patients with advanced BK (3) , central corneal thickness (CCT) was considered to be an important variable, although it exceeded the upper limit for ultrasound pachymetry.…”
Section: Introductionmentioning
confidence: 99%
“…Também com a lesão do plexo corneano ocorre a diminuição da sensibilidade corneana. Além disso, a cicatrização da córnea induz um aumento de proteínas extracelulares como laminina, fibronectina, colágeno tipo IV e hemidesmossomos, os quais promovem maior adesão entre epitélio e estroma (31)(32)(33)(34)(35) . O mesmo raciocínio é usado para a ceratectomia lamelar automatizada, só que neste caso, a remoção de tecido corneano é feita com uso de microcerátomo tradicional, que retira um disco com 160 μ, substituindo a fotoablação com o ¨excimer laser¨.…”
Section: Tratamentounclassified